Land management in Vietnam in the context of digital society - Vu, Thuong Thi.; Hoang, Huong Thi.; Nguyen, Thao Thu. (International Journal of Innovative Research and Scientific Studies, 2025)
The Vietnamese real estate market is evolving in a complex and volatile manner, affecting land management activities. In fact, many problems arise when new technologies are applied, facilitating people's land transactions, but also posing requirements for innovation in management activities. Digital technology is developing; the goal of digital transformation, building a digital government, and developing a digital society is being widely deployed, requiring digital knowledge and skills for civil servants and citizens to improve the effectiveness of social management activities, including land management. This study addresses land management and land management efficiency in Vietnam and the requirements within the scope of technological factors, including digital data, digital civil servants, and digital citizens; these requirements play a role as factors that directly affect land management. The research model is built with scales including "Land Management", "Digital Data", "Digital Civil Servants", and "Digital Citizens". The author conducted a survey of 600 leaders of commune-level government agencies from three provinces representing three regions of Vietnam, including Bac Ninh Province (North), Nghe An Province (Central), and An Giang Province (South). The research and survey results help identify the practice of land management and factors affecting land management, from which the author draws research conclusions and discusses policies to improve the effectiveness of land management in Vietnam.